Oxytocinergic input from the paraventricular nucleus to the nucleus accumbens core modulates methamphetamine-conditioned place preference - Ying-jie Cheng; Gui-ying Zan; Ying-zhi Deng; Di Deng; Man-qing Wu; Jing-rui Chai; Yu-jun Wang; Jing-gen Liu; Min Zhao (Nature Communications)
Abstract Methamphetamine (METH) is a highly addictive psychostimulant, yet its addiction mechanisms remain unclear. Oxytocin (OXT), a neuropeptide, shows promise in reducing METH addiction, but how OXT exerts its effects is poorly understood. Using conditioned place preference (CPP), we first found that intranasal OXT other than Arginine Vasopressin (AVP) administration suppressed METH-CPP in mice, which could be reversed by OXT receptors (OXTRs) blockade in the nucleus accumbens (NAc) core. Activating OXTRs in the NAc core similarly reduced METH-CPP. Then, we found repeated METH exposure inhibited oxytocinergic neurons within the paraventricular nucleus (PVN) and lowered PVN OXT protein level. Chemogenetic activation of PVN oxytocinergic neurons (PVNOXT) blocked METH-CPP. Furthermore, METH inhibited PVNOXT-NAc core circuit other than PVNOXT-NAc shell circuit. Activation of PVNOXT-NAc core circuit significantly inhibited METH-CPP. This study reveals METH may impair the endogenous OXT system, especially the PVNOXT-NAc core circuit, highlighting OXT’s therapeutic potential for METH use disorder (MUD).